Reducing Cognitive Load using Social Persuasion Prompts in Mathematics Multimedia Learning - Murtianto, Yanuar Hery; Retnowati, Endah; Hanham, Jose (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Although self-efficacy is widely acknowledged as a key to academic success in mathematics, limited research has examined how social persuasion strategies can be systematically integrated into multimedia learning to enhance self-efficacy and manage cognitive load. This study addresses the gap by examining the effects of integrated social persuasion prompts within mathematics instruction, focusing on cognitive load, self-efficacy, and problem-solving achievement. The first experiment compared worked example-based instruction with and without social persuasion, involving 66 undergraduate students enrolled in a multivariable calculus course for the first time. Instructional materials on parametric equations were delivered in a printed booklet and designed in alignment with Cognitive Load Theory. Social persuasion prompts were written on top of each worked example and problem-solving. The findings revealed that there was no significant different impact of written social persuasion, however the social persuasion significantly reduce cognitive load but increase self-efficacy. The second experiment recruited another 56 undergraduate students enrolled in the same multivariable calculus course studied the same worked examples in the format of multimedia. The results demonstrated that there was a strong impact of audio social persuasion on worked examples with regards to achievement, cognitive load, and self-efficacy level. This study provides profound evidence for integrating social persuasion in worked examples as it could enhance achievement, lower cognitive load, and improve self-efficacy. Further research on audio-based persuasion in multimedia format is discussed.